Sex Education for my Preschooler (ages 3 to 5)? Parents’ Perceptions - Cevallos-Neira, Ana Cristina; Jerves-Hermida, Elena Monserrath (Revista Electrónica Educare, 2014)
This investigation was conducted as a result of the lack of studies, specifically on children’s sex education and the role that parents play in it, despite the major advances in the knowledge on sexuality and its education. The main goal of this qualitative study was to understand parents’ perceptions regarding sexual education of their children ages 3 to 5. Three focus group sessions were conducted with parents from Cuenca pre-schools. Data was processed using thematic analysis. The study indicated that parents have a limited conception of sexuality, completely based on the biological aspect. In addition, it was clear that parents have traditional ideas, conceptions and beliefs, which are reflected when educating their children. This research shows parents’ lack of knowledge about sexuality and sex education and gives important data about the need for parents and the school to work jointly to provide children with adequate and appropriate sex education, as well as the need for parent training in order to establish a common language between home and school and to avoid a double discourse in children’s education and to ensure a proper implementation of sex education programs at this level.